2014
DOI: 10.1002/bmc.3321
|View full text |Cite
|
Sign up to set email alerts
|

Serum fatty acid profiles and potential biomarkers of ankylosing spondylitis determined by gas chromatography–mass spectrometry and multivariate statistical analysis

Abstract: Ankylosing spondylitis (AS) is a common chronic inflammatory rheumatic disease. Early and accurate detection is essential for effective disease treatment. Recently, research has focused on genomics and proteomics. However, the associated metabolic variations, especially fatty acid profiles, have been poorly discussed. In this study, the gas chromatography-mass spectrometry (GC-MS) approach and multivariate statistical analysis were used to investigate the metabolic profiles of serum free fatty acids (FFAs) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 37 publications
1
17
0
4
Order By: Relevance
“…Metabolomics is an emerging field of biomedical research that is based on characterizing the repertoire of small molecules in biological samples. Among a variety of techniques conventionally used for metabolite profiling, gas chromatograph–mass spectrometry (GC–MS) as a relatively low‐cost alternative has been widely used for the identification and quantification of metabolites to distinguish patients with diabetes (Liu et al, ), ankylosing spondylitis (Chen et al, ), Alzheimer's disease (Wang et al, ) and breast cancer (Lv & Yang, ). Recently, metabolomics coupled with multivariate statistical analysis has been also applied to plasma metabolite profiling for detecting systemic metabolic differences between POAG patients and controls (Burgess et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics is an emerging field of biomedical research that is based on characterizing the repertoire of small molecules in biological samples. Among a variety of techniques conventionally used for metabolite profiling, gas chromatograph–mass spectrometry (GC–MS) as a relatively low‐cost alternative has been widely used for the identification and quantification of metabolites to distinguish patients with diabetes (Liu et al, ), ankylosing spondylitis (Chen et al, ), Alzheimer's disease (Wang et al, ) and breast cancer (Lv & Yang, ). Recently, metabolomics coupled with multivariate statistical analysis has been also applied to plasma metabolite profiling for detecting systemic metabolic differences between POAG patients and controls (Burgess et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, Lecithin cholesterol acyltransferase (LCAT) is the key enzyme in this metabolic process, which can elevate the expression of APOA and further promote the clearance of cholesterol [73]. However, in this study, in ammatory conditions induced by AS decreased capacity of HDL and LCAT to e ciently transfer excess cholesterol in the ligament tissue to the liver, leading to the ectopic fat deposition in the ligaments of AS model mice [74]. Then, ectopic fat deposition could further promote the production of in ammatory cytokines, which resulted in cartilage dysfunction and degeneration in patients with AS.…”
Section: Lipid Metabolism Pathwaymentioning
confidence: 68%
“…In concordance, we observed that higher consumptions of SFA were more strongly correlated with BASFI score than MUFA and PUFA. Recently, serum free fatty acids have been shown as a biomarker of AS and some evidence of fat metaplasia in the pathogenesis of this disease has been revealed [25,26]. Moreover, diet strongly influences the composition of the gut microbiota in this regards diet rich in fat and carbohydrates might impact the gut microbiota of AS patients thus subclinical gut inflammation in AS might restrict the absorption and despite high energy intake in AS, BMI is not higher than controls [27,28].…”
Section: Discussionmentioning
confidence: 99%